Sensorless DTC of IPMSM for embedded systems - Terras Tahar; Hatani Kada (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The aim of this paper is to describe the sensorless control of interior permanent magnet synchronous motor (IPMSM) for electric vehicle (EV) using the Model Reference Adaptive System (MRAS) method for speed estimation. The algorithm of this method has been adapted with the mathematical model of the motorized wheels electric vehicle. The command used is the DTC. High performance sensorless drive of the in-wheel motor based on MRAS for electric vehicle and the whole system is simulated by Matlab/Simulink. The simulation results show the effectiveness of this proposed sensorless control strategy which is extensively used in electric vehicle application.